(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cancer may be a disease in which uncontrolled growth of cells begins in human body and this growth spreads to other organs of body. When cells get older or damaged, new cells take their place. Sometimes this process breaks down, and abnormal or damaged cells grows, multiply when they shouldn’t. These cells will form tumors, which are visible tissue lumps. Tumors can be cancerous or not cancerous (benign). Melanoma is a kind of cancer disease which begins in cells that grows as melanocytes, which are make melanin (the pigment that gives skin its color). Most melanomas form on skin, melanomas can also form in other pigmented tissues, during the year 2017, 96 lakhlives are estimated to died from the varied sorts of cancer. Every 6th death on our planet earth is due to cancer disease, making it the 2nd leading explanation for death – second only to diseases related to heart.biosensorsare used to detect a biological analyte’s, biosensorstransduceanalyte’s characteristics into an electrical signal that can be analyzed. Proposed work comprised a novel of Photonic Crystal structures for the carcinogenic sensing application consist of two types of resonator to a complex bus waveguide so as to achieve high quality factor and high sensitivity. Sensor is designed and analyzed in Rsoft photonic design software. Novel design is achieved by creating two types of resonator i.e. triangular and ring resonators connecting to a bus waveguide.For both the types FDTD simulations are performed for the detection of melanoma cancer cell. The sensitivity for rods in airconfiguration was found to be 1200nm/RIU and holes in slab was found to be 800nm/RIU respectively. Remarkable Q factor 2902 obtained during the simulation shows feasibility for future fabrication.